Pengaruh Brand Image dan Persepsi Harga terhadap Keputusan Pembelian Konsumen : Survei pada Konsumen Kedai Kopi 104 Singaparna - Kukuh Indra Liswana; Kusuma Agdhi Rahwana; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of simultaneous and partial brand image and price perception on purchasing decisions at Kedai Kopi 104 Singaparna. The research method used in this study is a quantitative approach with survey methods. The population in this study amounted to 100 respondents. The type of data used in this study is primary data obtained through a questionnaire. The data analysis used is the classical assumption test and multiple regression analysis using SPSS version 24. The results of this study indicate that brand image and price perception simultaneously have a significant effect on purchasing decisions at Coffee Shop 104 Singaparna. Brand image partially has a significant effect on purchasing decisions at Kedai Kopi 104 Sinagparna. Price perception partially has a significant effect on purchasing decisions at Kedai Kopi 104 Singaparna.